Prognostic value of platelet to lymphocyte ratio in patients with castration-resistant prostate cancer: a systematic review and meta-analysis - Ying, Junhui; Zhou, Changchun; Jin, Yili (Frontiers in Oncology, 2025)
IntroductionAlthough the platelet-to-lymphocyte ratio (PLR) has been identified as a prognostic marker in various cancers, its role in castration-resistant prostate cancer (CRPC) remains uncertain. This meta-analysis examines the prognostic significance of PLR in relation to overall survival (OS) and progression-free survival (PFS) in patients with CRPC.MethodsWe systematically searched PubMed, Embase, Web of Science, and the Cochrane Library up to March 11, 2025. Two reviewers independently screened studies, extracted data, and assessed quality using the Newcastle–Ottawa Scale (NOS). Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Sensitivity and subgroup analyses explored heterogeneity and assessed result stability. All analyses were performed using Review Manager 5.4 and STATA 15.0.ResultsA total of 13 studies (14 comparison groups; 2,405 patients) were included. High PLR was significantly associated with shorter OS (HR = 1.62, 95% CI: 1.30-2.03), but not with PFS (HR = 1.25, 95% CI: 0.92-1.69). Subgroup analyses confirmed the association with poor OS in prospective studies, patients aged ≥72, European populations, those on hormone therapy, and studies using a PLR cut-off ≥150. Heterogeneity mainly arose from differences in study design, treatment, and region. Sensitivity analyses and Egger’s test confirmed the robustness of findings with no publication bias.DiscussionPLR is a significant predictor of OS in CRPC and may help guide clinical risk stratification. However, its role in predicting PFS is limited. Further prospective studies are needed to validate its clinical utility.